Exit, Sunk Costs and the Selection of Firms - Yves Richelle; Paolo Garella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
The paper analyzes the question of which cost characteristics are exhibited by the rms that exit an oligopolistic market when costs are asymmetric and firms can credibly be forced out by the remaining competitors. The main results are: (i) if reentry is impossible (due to the presence of large sunk costs), then the firm with the highest marginal cost function dtays in; if reentry is costless then the firm with the highest average cost exits. Consequenty sunk costs not only affect the number of firms in an industry, but they also enter the determination of the type of rms that resist predation.
Keywords: 330